THE CONSTRUCTION OF HAPPINESS SCHOOL PARADIGM IN NAKHON RATCHASIMA PROVINCE, THAILAND (Proceedings of the International Conference on Education, 2019)
Abstract: The research purposes were, to investigated the Happiness School (HS.) factor of  HS. and the paradigms construction of  HS. Nakhon Ratchasima Province, Thailand. The research was using Modifield delphi technique. The target group were 17 experts in Nakhon Ratchasima by mixed methodology between qualitative and quantitative research. The data collected by the documentary study, interviews and the questionnaire. The data analyzed by contents analyzing median and interquartile range. The research found that ; HS. factors were the happiness at  students, teachers and staffs, school environment and the social and communities . The paradigms H.S. constructing were according to the H.S. factors. The process were; The student happiness: individual student, closing follow up, learning participation and active presenting. Staff happiness: Good Governance, school activity participation, collaborative promoting, constructing organizational culture, School environment: school area to livable learnable, providing learning resource to support the student learning, school cultural climate providing. Family and community happiness: participatory educational administration, organization collaborative promoting learning resource, school management reflecting..Keywords: maximum paradigms; happiness school
Keywords: maximum paradigms; happiness school